Exploring Okun's law asymmetry: An endogenous threshold LSTR approach - Dimitris Christopoulos; Peter McAdam; Elias Tzavalis (European Central Bank (ECB), 2019)
Using a novel methodology, we offer new evidence that a threshold relationship exists for Okun's law. We use a logistic smoothed transition regression (LSTR) model where possible threshold endogeneity is addressed based on copula theory. We also suggest a new test of the linearity hypothesis against the LSTR model. A combination of structural and policy-related variables accounts for changes (rises) in the Okun's parameter in the US in recent decades. Accordingly, the unemployment gap is increasingly associated with a smaller output gap. Whilst the Great Recession accelerated that rise, the bulk of the change occurred beforehand.
Keywords: C24; C46; E23; E24; 330; unemployment; output; asymmetries; logistic transition; endogeneity; copula; Monte Carlo; test for linearity